Manual Kepemimpinan dalam Naskah Sirāj al-Mulūk dan Serat Wulang Dalem: Perspektif al-Ṭurṭūshī dan Pakubuwono IX * - Ismail Yahya (Masyarakat Pernaskahan Nusantara, 2016)
Genre ”Mirror for Princes” -with its various terms- enlivened the Islamic literature, not only develop in Islamic centers in the Middle East, but also in other regions of the Islamic world, including Indonesia, more specifically Surakarta. One of the masterpieces of such a genre was Sirāj al-Mulūk by al-Ṭurṭūshī. The purposes of this study are to understand the background of the emergence of Sirāj al-Mulūk, to describe al-Ṭurṭūshī’s thoughts relating to leadership ethics, and try to relate it to Wulang Dalem, a work attributed to the Surakarta king of Pakubuwono IX. The findings of this study are: 1) socio-political contexts in the form of rebellion, disharmonious relationships between the government administration that occurred at the time of al-Ṭurṭūshī became the reason composing Sirāj al-Mulūk, 2) al-Ṭurṭūshī showed how politics and morality in Islam can not be separated, both are an integral and complementary, 3) this preliminary study found no direct link between the work of al-Ṭurṭūshī and PB IX, although found little common ground. === Genre ”Mirror for Princes” -dengan beragam istilah lainnya-menghiasi literatur-literatur Keislaman, tidak saja berkembang di pusat-pusat Islam di Timur Tengah, namun juga hingga ke kawasan lain dunia Islam, termasuk Nusantara, lebih spesifik lagi Surakarta. Salah satu karya dari genre tersebut adalah Sirāj al-Mulūk karya al-Ṭurṭūshī. Tujuan penelitian ini untuk memahami latar belakang kemunculan Sirāj al-Mulūk, mendeskripsikan pemikiran al-Ṭurṭūshī terkait etika kepemimpinan atau pemerintahan, dan mencoba menghubungkannya dengan karya raja Surakarta Pakubuwono IX, Wulang Dalem. Adapun yang menjadi temuan penelitian ini: 1) konteks sosial-politik berupa pemberotakan, ketidakharmonisan hubungan antar penyelenggara pemerintahan yang terjadi pada masa al-Ṭurṭūshī menjadi alasan menulis Sirāj al-Mulūk, 2) Pemikiran al-Ṭurṭūshī di dalam Sirāj al-Mulūk menunjukkan bagaimana politik dan moral di dalam Islam tidak dapat dipisahkan, keduanya merupakan satu kesatuan yang saling melengkapi, 3) dalam studi awal ini tidak ditemukan kaitan langsung antara karya al-Ṭurṭūshī dengan PB IX, walaupun ditemukan sedikit kesamaan gagasan.